Implementing a performant scheme interpreter for the web in asm.js. (September 2017) - Van Es, Noah; Stievenart, Quentin; Nicolay, Jens; D'Hondt, Theo; De Roover, Coen
Abstract: This paper presents the implementation of an efficient interpreter for a Scheme-like language using manually written asm.js code. The asm.js specification defines an optimizable subset of JavaScript that has already served well as a compilation target for web applications where performance is critical. However, its usage as a human-writable language that can be integrated into existing projects to improve performance has remained largely unexplored. We therefore apply this strategy to optimize the implementation of an interpreter. We also discuss the feasibility of this approach, as writing asm.js by hand is generally not its recommended use-case. We therefore present a macro system to solve the challenges we encounter. The resulting interpreter is compared to the original C implementation and its compiled equivalent in asm.js. This way, we evaluate whether manual integration with asm.js provides the necessary performance to bring larger applications and runtimes to the web. We also refactor our implementation to assess how more JavaScript code can cohabit with asm.js code, improving maintainability of the implementation while preserving near-native performance. In the case of our interpreter, this improved maintainability enables adding more complex optimizations. We investigate the addition of function inlining, for which we validate the performance gain. Highlights: A novel approach to efficient language implementation on the web is presented. Integrating asm.js in a JavaScript application can yield near-native performance. Frequently calling in and out asm.js components causes a significant overhead. Macros are proposed as a solution to write asm.js code by hand. Interoperability and optimal usage of asm.js and high-level JavaScript is discussed.